Vaccine Revolt: iconographic reading of the cover of Revista da Semana (1904) - Mercedes Neto; Francini de Souza Rodrigues; Daniella Cristina Julio Lima; Maria Jorgiane Otaviano de Abrêu; Tiago Braga do Espirito Santo; Ricardo Mattos Russo Rafael (Universidad de Alicante, 2019)
Objective: Analyze the symbolic elements on the cover of the 1904 of Revista da Semana on Vaccine Revolt as a means of imaging a social and sanitary movement. Method: This is a documental research that has utilized as a subject the preliminary phases of Erwin Panofsky's notions, pre iconographic and iconographic. Results: The vaccine's uprising portrayed on the cover of the magazine of the week of 1904 shows the imposition of sanitary measures by the government and the popular participation in the struggle against these abusive and vertical proposals with the risk prevention's speech. Conclusion: With this study it was possible to do a deepening about two characters who are opposite representatives in a society marked by determinants, social disparateness and politics that didn't assist the health and economical reality. And it also portrayed the power relationship in force at the time steps that culminated in the movement of Vaccine Revolt were implemented.